Langkah Langkah Strategis Pencegahan Dan Pengendalian Tuberkulosis Pada Unit Pelaksana Teknis Pemasyarakatan - Rafi Rizaldi; Padmono Wibowo (Poltekkes Kemenkes Malang, 2020)
Tuberculosis or TB is a major global health and public health problem including the correctional UPT environment. The condition of overcapacity and inadequate infrastructure are urgent for taking strategic steps to control and prevent TB in the correctional UPT. The results showed that the Ministry of Law and Human Rights took steps to control and prevent TB through the Four Pillars of Control, namely the managerial pillar, administrative control pillars, environmental control pillars and pillars of control with personal protective equipment. In addition, several steps were taken by the Correctional UPT, namely contact investigations for TB suspects and cases as well as prevention of transmission through family and community members by prisoners or correctional officers